MANAGING ETHNICITY, RELIGION, RACE, AND INTER-GROUP RELATIONS ISSUES: MULTICULTURALISM ISLAMIC EDUCATION - Fajar Syarif (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2020)
The prejudice and conflict caused by differences of tribe, faith, and group as well as students background can be pressed by multiculturalism of Islamic education. The Islamic education gives positive influence to acknowledgement and appreciation of differences in tribe, faith, and students’ background. The implementation of Islamic education learning in the multiculturalism perspective can be seen in the application of cooperative learning model where various groups (tribe, faith, race and intergroup) allows students to interact across culture so that students can have multicultural competencies.